2021
DOI: 10.1111/1759-7714.14013
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact according to the proportion of the lepidic subtype in stage IA acinar‐predominant lung adenocarcinoma

Abstract: Background: Adenocarcinoma is the most common type of lung cancer and most adenocarcinomas have heterogeneous subtypes. Acinar-predominant adenocarcinoma is the most common. This study aimed to identify the prognostic impact of other mixed histological subtypes in acinar-predominant lung adenocarcinoma. Methods: The medical records of patients with pathological stage IA acinarpredominant lung adenocarcinoma between January 2010 and April 2016 were reviewed. The patients were divided into two groups according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Invasive lung adenocarcinoma has mixed subtypes, and a favorable prognosis may be associated with the lepidic subtype proportion. 16,17 Solid or MP predominant subtypes are known as highgrade malignancies in invasive lung adenocarcinoma. 18 Many studies have been found on solid or MP predominant subtypes, which are associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive lung adenocarcinoma has mixed subtypes, and a favorable prognosis may be associated with the lepidic subtype proportion. 16,17 Solid or MP predominant subtypes are known as highgrade malignancies in invasive lung adenocarcinoma. 18 Many studies have been found on solid or MP predominant subtypes, which are associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lepidic predominant invasive lung adenocarcinoma has also been reported to have favorable outcomes as a low‐grade malignancy. Invasive lung adenocarcinoma has mixed subtypes, and a favorable prognosis may be associated with the lepidic subtype proportion 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, the analysis of these factors found different predominant subtypes did have different long-term OS and DSF effects. Specifically, the low-grade group had a better prognosis ( 2 ), and the high-grade group, which includes solid and micropapillary tumors, was frequently associated with a poor prognosis ( 16 , 24 - 27 ). This is consistent with results from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is a common malignant tumor with a high mortality rate ( 1 ), and lung adenocarcinoma (LUAD) is currently the most common histological subtype of non-small cell lung cancer ( 2 ). A new classification method of lung cancer was provided by the American Thoracic Society (ATS), the European Respiratory Society (ERS), and the International Association for the Study of Lung Cancer (IASLC) in 2011 ( 3 ) and was published by the World Health Organization (WHO) in 2015 ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies analyzed the risk of patients with lung adenocarcinoma based on the primary histological component or the proportion of second most predominant component [ 18 , 19 ]. Our study was based on the basic distribution of pathological components of the area adjacent pleura, including pathological components type of the area adjacent pleura within lesion, the shortest distance between the largest invasive component area and the pleura, the depth of the largest invasive component area.…”
Section: Discussionmentioning
confidence: 99%